Development of simulation model of centrifugal blowers for gas pumping unit taking into account bypass - Семенцов, Георгій Никифорович; Лагойда, Андрій Іванович; Когутяк, Мирослав Іванович (Technology audit and production reserves, 2016)
After a thorough analysis of failures in the compressor stations that operate centrifugal blowers Ц-16, which are the object of this research, it was found that a significant proportion of failures are the failures caused by surge phenomenon (25 %). One way to improve reliability is to introduce of high-speed multi-parametric and fuzzy controllers in a system structure that will prevent a surge. Gas dynamic characteristics of a centrifugal blower are approximated by regression model as a quintic polynomial. Characteristics of anti-blowing valve were approximated by a quintic polynomial, and characteristics of the actuator – derived from an active experiment, where rotation angle of the actuator output shaft was fixed by position sensor for abrupt change of the control signal. Moore-Greitzer model was used for describing of blower dynamics. Based on the above parameters obtained from the studies, simulation model of centrifugal blower of compressor unit that synthesized in the software Matlab will make it possible to simulate surge phenomenon. Based on the developed simulation model of automatic anti-surge control (ASC) system, multi-parametric and fuzzy controllers were synthesized. They were shown high rates of ASC speed.